Analisis Deskriptif Inovasi Sistem Relay Proteksi untuk Mencegah Kerusakan EMCP pada Unit Genset di PT PPA Jobsite MIP - Triraharjo, Joko; Kurniawan, Fika; Saputra, M. Ferry; Dendang, Adrianto; Nugroho, Edi Setyawan; S, Aryo Adi; L, Bagus Budhi Bowo (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Disruption of electricity supply is one of the main factors hampering industrial productivity, especially in the mining sector that relies on independent power plants such as generators. PT Putra Perkasa Abadi (PPA) experienced repeated problems related to damage to the Electric Module Control Panel (EMCP) in the Caterpillar 400 KVA generator set due to a sudden surge in current. This study aims to describe the process of implementing an additional protection system in the form of a protection relay and evaluate its effectiveness in preventing EMCP damage. This research uses a descriptive qualitative approach by collecting data through observation, interviews, and studies of the company's internal documentation. The results showed that the protection relay system was able to eliminate the frequency of EMCP damage to zero incidents, reduce downtime from 7 days to 30 minutes, and reduce replacement costs from Rp34,000,000 to Rp100,000 per incident. This innovation also has a positive impact on the aspects of Quality, Cost, Delivery, Safety, and Morale (QCDSM). This study suggests the application of protection relays as a safety system standard in mining industry generators and the need for further studies with a technical-quantitative approach to measure system performance more accurately.